A subgroup method based on the equivalent Dancoff-factor cell technique in APOLLO3® for thermal reactor calculations. (May 2020) - Mao, Li; Zmijarevic, Igor; Sanchez, Richard
Highlights: EDC method is coupled to the SG + SPH method in APOLLO3®. EDC method can reduce CPU time by a factor up to 50 against MCA method. In geometry of similar resonant pins, EDC and MCA obtain similar precision. In geometry of totally different resonant pins, EDC outperforms MCA in precision. SG + SPH method with EDC technique is efficient and precise. Abstract: The equivalent Dancoff-factor cell (EDC) method was implemented in APOLLO3® and was coupled to the newly developed subgroup method based on mathematical probability tables and on SPH corrections. The EDC method reduces a factor up to 50 in the self-shielding time in PWR assembly calculations, compared with the Multi-Cell Approximation (MCA) of the collision probability method. The EDC method avoids the similar material assumption (SMA), which can cause the MCA calculation an error of more than 600 pcm in k eff in assembly calculations with totally different resonant materials. In UOX and MOX cell depletion calculations, the errors due to the SMA in both the EDC and MCA methods are limited to less than 50 pcm. This work demonstrates that the EDC-based subgroup method is accurate and efficient for PWR fuel cell and assembly calculations.